Performance evaluation of Rayto RT-7600Vet hematology analyzer in side-by-side comparison with manual hematological methods for apparently healthy Cholistani cattle blood - Umer Farooq; Mushtaq Hussain Lashari; Zia Ur Rehman; Musadiq Idris; Haroon Rashid; Shagufta Nasreen; Farah Laraib; Rubaisha Ameer; Maryam Chauhdary; Iram Fatima (PLoS ONE, 2025)
The present study is the first from Pakistan being reported with an objective to assess performance of Rayto RT-7600Vet hematology analyzer (HA) for Cholistani cattle blood (n = 134), in comparison to the manual hematological methods. The four hematological attributes viz. total erythrocyte count (TEC), hemoglobin (Hb), packed cell volume (PCV) and platelet count (PLT) were deduced through HA (A) and manual (M) methods. Various statistical tests were implied to ascertain level of interrelationship, accuracy and level of agreement between the two methods. All attributes attained through manual methods had high positive, leptokurtic distribution (having many outliers) except for PLT-M and PCV-M. The coefficient of variation for attributes attained through HA and manual methods ranged from 16–24% and from 16–59%, respectively. Comparison between the overall results revealed that all the studied attributes, except TEC, were significantly (P≤0.05) different for both methods. A weak relationship was noticed between the attributes attained through two methods as indicated by weak r-values and adjusted r-square values. The reliability level of estimating Hb and PCV had highest intraclass correlation coefficient value of 0.722 and 0.555 for average measures, respectively. However, accuracy level, as determined through Lin’s concordance correlation coefficient was highest for TEC (0.9504) for both analytical methods. Poor level of agreement, in general, was shown for the two methods of analysis regarding all four hematological attributes through Bland and Altman test. In conclusion, the Rayto RT-7600Vet) may present data having higher skewness, kurtosis, and CV%, however, they are valid for multi-species hematological analysis. Caution must however, be taken in interpreting their results with corrected reference intervals and CV% for each machine and for each tested attribute.